2017
DOI: 10.1007/s10792-017-0616-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of visual symptoms on the quality of life of patients with early to moderate glaucoma

Abstract: Vision-related QoL may be severely compromised in glaucoma patients with visual symptoms. Patients with visual disorders should be evaluated for glaucoma and QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…An interesting note is that despite different sociocultural backgrounds, the items were fairly similar in our questionnaire compared to the Go-QOL questionnaire, which was developed for a Dutch population. 10 In particular, facial disfigurement and the need for camouflage, social interaction and ability to perform daily activities were common items. This suggests that the QoL impact of TED may be similar across cultures and some of the QoL challenges are universally evident.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting note is that despite different sociocultural backgrounds, the items were fairly similar in our questionnaire compared to the Go-QOL questionnaire, which was developed for a Dutch population. 10 In particular, facial disfigurement and the need for camouflage, social interaction and ability to perform daily activities were common items. This suggests that the QoL impact of TED may be similar across cultures and some of the QoL challenges are universally evident.…”
Section: Discussionmentioning
confidence: 99%
“…QoL is a broad concept that assesses the impact of an illness on patients' physical, mental, social, and functional health. 7 Disease-specific factors, such as symptoms, treatment burden, inconvenience, and task-specific difficulty, have resulted in the development of several condition-specific QoL questionnaires in Ophthalmology, 8 10 including two for TED, namely the 15-item Graves' Ophthalmopathy-QOL (GO-QOL) and the 3-item TED-QOL. 6 , 11 However, as yet there is no TED-specific questionnaire to study the QoL impact of TED in adults in Asia.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was reported that glaucoma patients of African descent have no difference when compared with Caucasian glaucoma patients with respect to the NEI-VFQ-25 visual subscales [38]. Although no direct comparison to a Caucasian population was made, Korean glaucoma patients also have reported significant issues with the peripheral and social function vision subscales [39], and in a case-control comparison of Latino-Americans, significant differences were observed in all visual subscales [40]. A limitation of this study is the exclusion of participants with diabetic retinopathy, retinal detachment, and AMD-intentionally done to avoid including participants with secondary glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, even mild or moderate vision loss can reduce a person's productivity, restrict his social life and lead to a decline in mental health. Several studies have found that the severity of glaucoma correlates to reduced work performance that relies on eyesight, such as reading and driving [ 18 ]. As vision deteriorates, glaucoma can limit a person's independence by reducing their ability to perform activities of daily living.…”
Section: Introductionmentioning
confidence: 99%